Ascorbic and Dehydroascorbic Acid- Connections to Type 1 Diabetes - Ludvigsson, Johnny (Archives of Clinical and Biomedical Research, 2021)
The etiology of Type 1 diabetes (T1D) is unknown. While especially B- and D-vitamins have been to some extent studied in relation to development of Type 1 diabetes, Vitamin C has been ignored despite its important effects as an antioxidant protecting against oxidative stress, its influence on the immune function including autoimmunity, and the possible direct effects on the pancreatic beta cells. Recently the demonstration of increased dehydroascorbic acid before the development of autoantibodies in serum of children with genetic risk for T1D has drawn some attention to the ascorbic and dehydroascorbic acids, which decades ago have been linked to effects on the pancreatic beta cells. As long as there is no safe, efficacious and practical way of preventing Type 1 diabetes there are reasons to resume the interest for vitamins, including Vitamin C.